Apoptotic mechanism of human leukemia K562/A02 cells induced by magnetic iron oxide nanoparticles co-loaded with daunorubicin and 5-bromotetrandrin - Wang, Jun (Dove Medical Press, 2011)
The purpose of this study was to assess the induced apoptosis of self-assembled iron oxide magnetic nanoparticles (MNPs) co-loaded with daunorubicin (DNR) and 5-bromotetrandrin (Br Tet) (DNR/Br Tet-MNPs), acting as a drug depot system for the sustained release of the loaded DNR and BrTet, in the drug resistant human leukemia K562/A02 cells and further to explore potential mechanisms. After being incubated for 48 hours, K562/A02 cells were treated with DNR/Br Tet-MNPs or DNR and Br Tet in solution (DNR/Br Tet-Sol). Morphologic characteristics of K562/A02 cells were observed under a fluorescence microscope; cell apoptosis and intracellular accumulation of DNR were analyzed by FACS Calibur flow cytometry. Furthermore, reverse transcriptase polymerase chain reaction (RT-PCR) and Western blotting analyses were performed to study the apoptosis associated gene transcription and protein expression, respectively. Typical apoptotic characteristics, including chromatin condensation and fragmentation of nuclei, were observed and a high rate of apoptosis was detected in K562/A02 cells treated with DNR/Br Tet-MNPs and DNR/Br Tet-Sol. Detection of relative fluorescence intensity of intracellular DNR demonstrated that intracellular DNR was higher in K562/A02 cells treated with DNR/Br Tet-MNPs than that of DNR/Br Tet-Sol. Further study demonstrated that both DNR/Br Tet-MNPs and DNR/Br Tet-Sol reduced the gene transcriptions and protein expressions of bcl-2 and survivin and enhanced that of bax and caspase 3. It is concluded that self-assembled DNR/Br Tet-MNPs, as one of the potential antitumor agents for hematologic malignancies, may effectively induce apoptosis of K562/A02 cells through elevating the ratio of bax/bcl-2, activating caspase 3, and inactivating survivin.